Formic Acid Electro‐Synthesis by Concurrent Cathodic CO2 Reduction and Anodic CH3OH Oxidation. (15th December 2020) - Wei, Xinfa; Li, Yan; Chen, Lisong; Shi, Jianlin
Abstract: The electrochemical conversion of carbon dioxide into energy‐carrying compounds or value‐added chemicals is of great significance for diminishing the greenhouse effect and the efficient utilization of carbon‐dioxide emissions, but it suffers from the kinetically sluggish anodic oxygen evolution reaction (OER) and its less value‐added production of O2 . We report a general strategy for efficient formic‐acid synthesis by a concurrent cathodic CO2 reduction and anodic partial methanol‐oxidation reaction (MOR) using mesoporous SnO2 grown on carbon cloth (mSnO2 /CC) and CuO nanosheets grown on copper foam (CuONS/CF) as cathodic and anodic catalysts, respectively. Anodic CuONS/CF enables an extremely lowered potential of 1.47 V vs. RHE (100 mA cm −2 ), featuring a significantly enhanced electro‐activity in comparison to the OER. The cathodic mSnO2 /CC shows a rather high Faraday efficiency of 81 % at 0.7 V vs. RHE for formic‐acid production from CO2 . The established electrolyzer equipped with CuONS/CF at the anode and mSnO2 /CC at the cathode requires a considerably low cell voltage of 0.93 V at 10 mA cm −2 for formic‐acid production at both sides. Abstract : This work reports a strategy of substituting the anodic oxygen evolution reaction with thermodynamically flexible and kinetically favorable oxidation reactions for the efficient electrochemical conversion of CO2 . The same product, formic acid, can be obtained with a low cell voltage from both the anodic partial methanol oxidation reaction catalyzed by CuONS/CF and the cathodic CO2 reduction reaction catalyzed by mSnO2 /CC.